THE ROLE, ESSENCE AND CRITERIA OF SOCIAL COMPENSATION IN STUDENTS - Farhod Makhsiddinovich Norbo’tayev; Ahmadova F.Sh. (Journals Park Publishing, 2022)
This article covers the problem of compensation, the content of social competence, corporate system of social competence development, stages and pedagogical model.
Keywords: training; base; competence